PERSENTASE BAGI HASIL MUDHARABAH DAN RATE BUNGA DALAM PEMBERIAN MODAL USAHA MIKRO (STUDI KASUS BMT MUDA JATIM SURABAYA DAN KOPERASI K3PG GRESIK) - Abdul Majid Toyyibi; Anni Mujahidah Duta Pertiwi (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2021)
This study aims to determine the Percentage of Profit Sharing and Interest Rate in the Provision of Micro Business Capital. Researchers also want to know how many use financing from BMT MUDA and K3pg Cooperatives. The research method uses a qualitative approach. This type of research uses a descriptive-comparative method by comparing the data for profit sharing and interest rates in providing micro business capital at BMT MUDA East Java Surabaya and K3PG Petrokimia Gresik. The researcher collected data by using observation, interview and documentation techniques. The results of research conducted by researchers on BMT MUDA and K3PG Cooperatives are more dominant in K3PG because in repayment of financing, K3PG is automatically deducted from the monthly salary. Meanwhile, in MUDA BMT, the payment is from the results of the managed business.